Pengenalan Coding Dasar bagi Guru SMA sebagai Upaya Peningkatan Literasi Digital dalam Pembelajaran - Hidayat, Syamsu; Rifiyanti, Hafizah; Angellia, Filda; Nasution, Taruna; Kurniawan, Ari (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
The rapid development of digital technology requires teachers to improve their digital literacy and integrate technology into the learning process. However, many senior high school teachers still have limited understanding of basic coding concepts and their application in classroom activities. This community service program aimed to introduce fundamental coding concepts and enhance teachers' digital literacy to support innovative learning practices. The method used included socialization, hands-on training, and mentoring using simple coding platforms. The program was conducted in Kecamatan Jagakarsa, South Jakarta, involving 15 teachers from various subject backgrounds. The activities were implemented through preparation, execution, and evaluation stages. The results indicated an improvement in participants’ understanding of basic coding, logical thinking, and its application across subjects. Participants also showed positive responses and increased motivation to integrate coding into their teaching practices. Therefore, this program contributed to strengthening teachers’ readiness to face digital transformation in education and encouraged the integration of computational thinking in classroom learning.